Uresničevanje verske svobode v praksi Evropskega sodišča za človekove pravice - Letnar Černič, Jernej (Bogoslovni vestnik, 2016)
The right to freedom of religion is one of the cornerstones of a free, pluralistic, tolerant and broadminded democratic society. However, it is not absolute but is protected within the context of other values. The article discusses and analyses over twenty most important cases concerning the exercise of religion in public space from the case load of the European Court of Human Rights. The Court protects freedom of exercise of religion based on the values of pluralism, tolerance and state neutrality, thereby taking into account the urgent social needs in every European society. In conclusion, it is individuals who are responsible for creating tolerant, pluralistic and free exercise of religion in public space in their respective European societies.
Keywords: človekove pravice; human rights; svoboda veroizpovedi; mednarodna sodišča; Evropsko sodišče za človekove pravice; sodna praksa